Cu Film Characteristics Synthesized Using Electrodeposition Technique at Various Currents and Under a Rotating Neodymium Magnet - Susetyo, Ferry Budhi; Basori; Mansor, Muhd Ridzuan; Ruliyanta; Yudanto, Sigit Dwi; Rosyidan, Cahaya; Situmorang, Evi Ulina Margareta; Edbert, Daniel; Mutiara, Etty; Yulianto, Tri; Agus Jamaludin; Nanto, Dwi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
In the present study, Cu films were made over Al alloy using the electrodeposition technique. Electrodeposition conducted at various currents (80, 100, and 120 mA), with and without influence by a rotating magnetic field (100 rpm of rotation). 0.5 M CuSO4 + 20 mL of H2SO4 was used for electrolyte solutions. The sample before and after electrodeposition was weighed using digital scale to calculate deposition rate and current efficiency. All formed Cu films were characterized using X-ray diffraction (XRD), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), Scanning electron microscopy equipped with Energy dispersive spectroscopy (SEM-EDS), and Potentiostat apparatus. Furthermore, antibacterial activity using Staphylococcus aureus was also investigated. Increasing the current of electrodeposition leads to an increase in deposition rate and current efficiency for both conditions (with and without rotating magnetic field influence). Based on the XRD and ATR-FTIR investigation, Cu was successfully deposited onto Al surface. Currents used for the electrodeposition process between 80-100 mA would result in a faceted structure, while using 120 mA results near to spheroidal. Shifting to higher currents leads to decreases in grain sizes and presenting a rotating magnetic field also enhances the grain size. Current and rotating magnetic influences are not linearly influencing corrosion potential, corrosion rate and antibacterial activity. The sample made using higher current plus influencing with a rotating magnetic field has less corrosion rate and higher area of inhibition at around 0.808 mmpy and 4.01 cm2.